KEEFEKTIFAN MODEL STUDENT FACILITATOR AND EXPLAINING BERBANTU MEDIA PAPAN KARTU TEMPEL TERHADAP HASIL BELAJAR SISWA KELAS IV TEMA CITA-CITAKU SDN 01 GEMUHBLANTEN - Sri Rahayu; Qoriati Mushafanah; Veryliana Purnamasari (FKIP, PGSD, Universitas Slamet Riyadi, 2019)
This research aimed to determine the effectiveness of the Student Facilitator and Explaining models with the help of the Paste Card media on the learning outcomes of the fourth grade students on the theme of My Story SDN 01 Gemuhblanten. The population were all fourth grade students of SDN 01 Gemuhblanten Kendal academic year 2018/ 2019. This research was an experimental study with a quantitative approach. The design of this study was a pre-experimental study with the type of research used is one group pretest-posttest design that uses a sampling technique that is non probability sampling. Data collection techniques are carried out using interview, observation, documentation, and test techniques. Student learning outcomes are seen from the average pretest value of 59.00 and increase in the posttest value with an average of 83.37. From the calculation of t-test obtained tcount greater than ttable that is 20,391>2,101, then H0 is rejected and Ha is accepted. The conclusion is that the Student Facilitator and Explaining learning model is assisted by the media of the Paste Card Board effective on the learning outcomes of the fourth grade students on the theme of My Story SDN 01 Gemuhblanten.